(3MGTjI Ydi GdHgGFjIs - (3GdeGFj GdMdHj , YeQ Hf CMeOs
(3ChdgG (B:s
(3jG ef YLR Yf LeY JVGYa fYeg CbdGe CagGe GdYbdGA CeG HYO ajbhd GdabjQ Edi Gddg GdZfi Efi QSeJ ajeG eVi ai CjGe GdJMUjd JYdjbGJ Ydi GdehGVY GdeTcdI s
(3BNQgG (B:s
(3GdeSFdI GdChdi ef GdeaQOGJ aCbSe GdYOO hgh NeSI hSHYhf Ydi YOO GdCTjGA hgh YTQI jNQL SHYI hfUa hgh GdeLghd GdZGFH ai GdeGA hgPG BNQ GdcdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs